P103 Characterisation, prediction, and impact of readmission within 90 days of surgery for non-small cell lung cancer. (11th November 2022) - Roberts, EG; Shalom, N; Scholes, H; Gleeson, H; George, HA; Rao, JN; Socci, L; Hopkinson, DN; Tenconi, S; Edwards, JG
Abstract : Introduction: Lung Cancer Clinical Outcomes Project publications give a median 90 Day Readmission (90DR) rate of over 40%. The reasons for and impact of 90DR have not been characterised. The aims of the study were to characterise and determine predictors for 90DR and examine its clinical impact. Methods: A retrospective analysis of NSCLC surgery patients between 02/12/2008 and 01/04/2021, referred from a tertiary centre Lung MDT, for whom clinical and Hospital Episode Statistics (HES) data were available. HES diagnostic codes were interrogated for co-morbidities and the reason(s) for 90DR. Three disparate categories for 90DR were derived, based on 13 underlying reasons for 90DR. Correlations were assessed using standard statistical methods and binary logistic regression models predicting 90DR created. The survival impact of the 90DR categories was examined in univariate and multivariate models. Results: After the exclusion of patients referred from other hospitals, 1043 patients remained in the study. 90DR occurred in 302 (28.9%) patients, of which almost half were due to adjuvant chemotherapy administration (46.8%): the most common surgical complication was pulmonary (14.3%). Tumour Related Readmission (TRR), Surgical Related Readmission (SRR) and Unrelated Readmission (UR) occurred in 8.6%, 11.2% and 9.1% of patients respectively. Independent predictors of TRR were tumour stage (T-stage, p = 0.049 and N-stage, p = 0.005), and completeness of resection (p = 0.03). Independent predictors of SRR were the absence of hypertension (p < 0.001), asthma (p = 0.005), and operations converted from VATS to thoracotomy (p = 0.010). Both TRR and SRR were associated with worse survival (median survival 49.6 months (p = 0.013) and 63.4 months (p = 0.016), versus 83.6 months for no 90DR): however, SRR readmission was not an independent predictor of survival (p = 0.45). Conclusion: Whilst prediction of SRR may be possible, SRR may not have lasting clinical impact. However, the methodology of this study could be exploited on national databases to determine whether their multivariate prediction could lead to interventions to reduce the health economic impact of 90DR.